FOOD SAFETY IN THE PERSPECTIVE OF THE SUNNAH: A STUDY OF HADITH ON COVERING FOOD - Muhammad Fikri Alhariez; Irfan Yuhadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Food safety is a critical issue in maintaining public health linked with safe and clean food for preventing diseases. From a Sunnah perspective, the principles of food safety are not only viewed from a physical cleanliness standpoint but also from a spiritual perspective taught by the Prophet Muhammad (peace be upon him). This study aims to examine the relevance of the Sunnah teachings regarding the practice of covering food in the context of food safety. The study is conducted by a qualitative approach using a literature review method. This research analyses Hadiths that discuss the importance of covering food and its implications for preventing contamination and food poisoning. The hadiths come from authentic sources narrated by Sahih Muslims and Imam Hanbal, therefore, hold a very strong position in the Sunnah. The findings of this study indicate that covering food in the Sunnah serves not only as a practical measure to maintain cleanliness and prevent contamination by microorganisms but also carries a philosophical and spiritual dimension that teaches Muslims to be grateful and mindful of the blessings of food. The study also highlights the importance of integrating religious teachings with modern principles of food safety as part of efforts to prevent foodborne diseases.